Clinical Significance of Serum Galectin-9 and Soluble CD155 Levels in Patients with Systemic Sclerosis. (27th November 2018) - Chihara, Mami; Kurita, Miki; Yoshihara, Yuki; Asahina, Akihiko; Yanaba, Koichi
Abstract : Signaling through coinhibitory receptors downregulates the immune response to prevent excessive immune activation and maintain optimal immunity and tolerance. The aim of this study was to examine the levels of the soluble forms of coinhibitory receptors and their ligands, namely, galectin-9 (the ligand of T-cell immunoglobulin and mucin domain 3) and CD155 (the ligand of T cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain), and their association with clinical features in patients with systemic sclerosis (SSc). The serum levels of galectin-9 and soluble sCD155 were examined by enzyme-linked immunosorbent assays in patients with SSc, and the results were evaluated with respect to clinical features. Patients with SSc exhibited raised serum levels of galectin-9, but not sCD155. Serum galectin-9 levels were raised not only in patients with diffuse cutaneous SSc but also in patients with limited cutaneous SSc. Furthermore, serum galectin-9 levels correlated positively with the erythrocyte sedimentation rate. In addition, increased serum galectin-9 levels tended to be associated with higher mortality and serious organ involvement. These results suggest that galectin-9, but not CD155, may be involved in the pathogenesis of SSc. In addition, the measurement of serum galectin-9 levels could be used to predict serious organ involvement and high mortality in patients with SSc.